Tragedy according to Plato’s critical opinion - Kastrati, Nexhmije (Technium Social Sciences Journal, 2022)
The ancient Greek world gave world literary philosophy great names such as Plato, Homer, Aeschylus, Sophocles and others who revolutionized the art of writing and told it the idea of critical thinking, on the forms, styles and skills of making art generally. In ancient antiquity these attitudes were primary, and it was almost impossible for the writings to break away from the tradition, which at its core was dominated by tragedy, as one of the formats that would later dominate the entire globe as a source of inspiration. Man seems to need to experience loss, suffering and tragedy, perhaps to appreciate the love and spirit that it (life) gives. Therefore, in this paper, the types of dramatic works are taken for analysis, in particular the tragic and the tragedy according to the critical opinion of Plato, and the development of this field in old Greece, with the most famous authors Aeschylus and Sophocles and with Shakespeare in Europe. A special space in this study is occupied by Plato’s criticism of Homer, to whom he even asked special questions, because, as is known, Plato in his theory on the state was looking for a literature, an art that would have educational effects on young people ...as well as the theoretical problems that characterize tragedy, the hero and heroism and other feats, and the writing style within the literary narrative.